PERIPHERAL ISLAM: A Critique of the Epistemic Marginalization of Southeast Asian Islam - Hanafi, Imam; Maulana, Maulana (Asia-Pacific Journal on Religion and Society, 2024)
This paper examines the phenomenon of "peripheral Islam," often attributed to Southeast Asian Muslim societies within global Islamic historiography. Using a qualitative and literature-based approach, supported by center-periphery theory, epistemic marginalization, and postcolonial theory, the article reveals how hegemonic narratives—shaped by Orientalists and Arab-centric standards—have reduced Southeast Asian Islam to a secondary and inauthentic form. The study finds that the Malay-Nusantara region possesses a strong intellectual heritage, transnational scholarly networks, and local religious practices rich in epistemic and cultural resistance. By highlighting the role of pesantren (Islamic boarding schools), Malay Islamic literature, and local Islamic models such as Islam Kejawen and Islam Hadhari, this paper asserts that Southeast Asian Islam is an integral and contributive part of global Islamic civilization. The article calls for a reconstruction of perspectives on Southeast Asian Islam, viewing it not as a periphery, but as an alternative center within a plural, contextual, and transformative Islam.